Supervizija, stres in poklicna izgorelost šolskih svetovalnih delavcev - Kovač, Jernej (University of Maribor Press, 2013)
Supervision, Stress and Professional Burnout of School Counselors. In the work of dr. Jernej Kovač sheds light on the phenomena of stress and occupational burnout of school counseling staff at school and the role of supervision in overcoming and preventing these phenomena in the work of school counseling services or school counselors. In his work, the author deals with very important aspects and phenomena, which are becoming more and more frequent in school counseling and must be dealt with in-depth, with a great deal of human sensitivity and professional responsibility. The theoretical lighting and operational guidance for such work can be found in the present work by school counselors and others interested in this issue. In it, the author opens up a new dimension of school counseling work, completes and deepens it. Delo dr. Jernej Kovac: Supervision, Stress and Occupational Burnout of School Counselors Opens a New, Increasing Dimension of School Counseling Work, Expands the Framework and Supplements the Theory of School Counseling Work educational work in school.